The Influence of the Local Varieties on the Sound Patterns of English: A Case Study of Bangladeshi Tertiary Students - Hoque, Muhammad Azizul (IIUC Studies, 2012)
This paper is an outcome of the study that was directed to investigate the influence of the local varieties on the sound patterns of English of Bangladeshi tertiary students. The study deals with the existing pronunciation style and tries to identify the problems in the light of the rural background of the students. The study is qualitative by nature illuminating qualitative data, and the methods of data collection consist of record keeping of words through direct interview, reading passages and dialogues. The results of the study are the mispronunciation of English words because of the influence of local varieties, ignorance and lack of the Standard English pronunciation system, etc. On the basis of the findings, some pedagogical implications and recommendations have been made. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12268 IIUC Studies Vol.7 2011: 197-220